Characterization of Ferrofluid-Based Stimuli-Responsive Elastomers - de Pedro, Sandra; Muñoz-Berbel, Xavier; Rodríguez-Rodríguez, Rosalia; Sort, Jordi; Plaza, Jose A.; Brugger, Juergen; Llobera, Andreu; Cadarso, Victor J. (Frontiers in Mechanical Engineering, 2016)
Stimuli-responsive materials undergo physicochemical, and/or structural changes when a specific actuation is applied. They are heterogeneous composites, consisting of a non-responsive matrix where functionality is provided by the filler. Surprisingly, the synthesis of Polydimethylsiloxane (PDMS)-based stimuli-responsive elastomers (SRE) has seldomly been presented. Here we present the structural, biological, optical, magnetic and mechanical properties of several magnetic SRE (M-SRE) obtained by combining PDMS and isoparafin-based ferrofluid (FF). Independently of the FF concentration, results shown a similar aggregation level, with the nanoparticles (NP) mostly isolated (>60%). In addition to the superparamagnetic behaviour, the samples show no cytotoxicity except the sample with the highest FF concentration. Spectral response shows FF concentrations where both optical readout and magnetic actuation can simultaneously be used. The Young’s modulus increases with the FF concentration until the elastomeric network is distorted. Our results demonstrate that PDMS can host up to 24.6% FF. When applied to soft microsystems, a large displacement for relatively low magnetic fields (< 0.3 T) is achieved. The herein presented M-SRE characterization can be used for a large number of disciplines where magnetic actuation can be combined with optical detection, mechanical elements and biological samples.